INDEPENDENSI HARIAN UMUM SINGGALANG DALAM KOMUNIKASI POLITIK PADA PEMILIHAN KEPALA DAERAH (PILKADA) DI SUMATERA BARAT - Saputra, Edi (Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
There had been some significant improvements made in the process of political communication during Pilkada (governor election) 2005 in West Sumatera. The fluency of political communication process was influenced by the independency of news paper including Harian Umum Singgalang as oneÂ mediumÂ to convey ideas, statement, and political messages given by the Pilkadaâ€™s candidate (cagub/cawagub). The independency of news paper was determined through its â€œTajuk Rencanaâ€. In the â€œTajuk Rencanaâ€, the editor was free to convey the ideas and thoughts without being influenced by any other parties, especially by the canditates. The news paper roled neutral by clearly extending the society perspective related to the problems occured in the Pilkada. Therefore, the news paper had roled as a political communication medium which acted independently to succeed the process of democracy in the Pilkada of 2005 in West Sumatera. Keywords: Independency, political communication, Regional Head Election